(untitled) (Medicine Today, 2024)
Introduction: Abnormal uterine bleeding describes any variation from normal bleeding patterns in nonpregnant, reproductive-aged women beyond menarche lasting for at least 6 months. Regular cyclic menstruation results the choreographed relationship between the endometrium and its regulating factors. Any type of disturbance between the regulatory mechanism of pituitary ovarian axis or pelvic diseases results in abnormal uterine bleeding. Thyroid hormones play a key role in the menstrual and reproductive function of women. It is recognized universally that menstrual disturbances may accompany clinical alterations in thyroid function. Objectives: To evaluate the thyroid dysfunction in patients with abnormal uterine bleeding. Materials and Methods: This cross sectional study was conducted in Department of obstetrics & gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from April 2023 to December 2023. Women with abnormal uterine bleeding were included in the study. Sample was selected by purposive sampling. Sample size was 100. Detail demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously. Data was collected by using a semi-structured questionnaire. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Result was presented in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc. Results: In this study, the maximum numbers of cases (43.0%) were between 26-35 years age group. Mean age was 29.57 ± 8.27 years. Large numbers of respondents came from urban area (58%). On evaluation of types & causes of AUB, maximum patient belongs to AUB-L (leiomyoma) group (53%) followed by AUB-A (adenomyosis) (28%); AUB-P (polyp) (8%); AUB-O (ovulatory) (9%) and AUB-M (malignancy) (2%). Present study showed that prevalence of thyroid disorders is 26% in AUB patients. The prevalence of Hypothyroidism was 18% and Hyperthyroidism was 8%. Thyroid dysfunction is associated with menstrual abnormalities in females of all age groups. Conclusion: Abnormal uterine bleeding has a strong association with thyroid disorders. The most common type of disorder is subclinical hypothyroidism. Thus, all patient of AUB must be evaluated for thyroid dysfunction. Medicine Today 2023 Vol.36 (1): 1-6